Optimization of a functional cookie formulation by using response surface methodology - Lee .L.Y,; Tan .K.S,; Liew .S.L, (Universiti Kebangsaan Malaysia, 2011)
A functional cookie formulation containing oligofructose, dietary fibre and lower calorie, fat and sugar contents than conventional cookies was optimized using Response Surface Methodology (RSM). Instant N-Oil II was used as a fat replacer, while Raftilose ®P95 was used as a sugar substitute with the addition of fructose to enhance sweetness. Selection of the optimal formulation was based on caloric content. An optimized formulation, V1, was obtained from the model Y = 4927.70 – 152.34X1 – 155.42X3 + 104.20X32 + 151.71X33 – 95.08X34, where Instant N-Oil II replaced 30% of butter and 24.4%, w/w (30.5g) fructose replaced 40.0%, w/w (50.0g) sucrose. Two additional optimized formulations, S1 and S2, were proposed which contained the same ingredients as V1, but both contained 19.0%, w/w (23.8g) Raftilose ®P95. Also, S2 had a higher fat replacement level (42%). A reference cookie prepared from a conventional recipe received significantly higher scores (P < 0.05) than the functional cookies V1, S1 and S2 in the sensory evaluation. However, when health benefits of the functional cookies were explained to the panel after the sensory evaluation had concluded, majority of the panelists stated that they would prefer S1, had they known of its health benefits. S1 contained 19.04% fat, 8.62% fructose and 0.74% sucrose, namely, significantly lower fat and sucrose levels and higher fructose content than the conventional cookie.